DETERMINAN KINERJA SISTEM INFORMASI AKUNTANSI: STUDI EMPIRIS PADA BANK SYARIAH DI WILAYAH DAERAH ISTIMEWA YOGYAKARTA - Marfuah Marfuah; Akbar Handoko (Faculty of Economics, Universitas Islam Indonesia, 2012)
This research is aim to analyze factors affecting the performance of accounting information system (SIA) of Islamic Banks in Daerah Istimewa Yogyakarta (DIY). The variables that are expected to influence SIA including the existence of monitoring board, formalization of information system, top management support, user involvement, technical skill of staff, organization size, training and education program, location of information system department, communication between user and developer, and user conflict . As many as 65 respondents were taken from 3 Islam banks in DIY. The research findings show that there are 6 variables that significantly influencing the performance of SIA, namely: the existence o fmonitoring board, top management support, user involvement, technical skill of staff, organization size, training and education program, location of information system department, communication between user and developer. Meanwhile, user conflict variable has negative influence on the performace of SIA. Formalization of information system variable and organization size variable have no influence on the performance of SIA.